2013
DOI: 10.1155/2013/740187
|View full text |Cite
|
Sign up to set email alerts
|

TrkAIII Promotes Microtubule Nucleation and Assembly at the Centrosome in SH-SY5Y Neuroblastoma Cells, Contributing to an Undifferentiated Anaplastic Phenotype

Abstract: The alternative TrkAIII splice variant is expressed by advanced stage human neuroblastomas (NBs) and exhibits oncogenic activity in NB models. In the present study, employing stable transfected cell lines and assays of indirect immunofluorescence, immunoprecipitation, Western blotting, microtubule regrowth, tubulin kinase, and tubulin polymerisation, we report that TrkAIII binds α-tubulin and promotes MT nucleation and assembly at the centrosome. This effect depends upon spontaneous TrkAIII activity, TrkAIII l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The marked difference in intracellular trafficking, cell surface expression and spontaneous activation exhibited by TrkA and TrkAIII in SH-SY5Y cells confirms the critical role played exons 6 and 7 encoded sequence in optimising intracellular trafficking from the ER to the GN, reducing intracellular spontaneous activation potential and promoting receptor maturation, an essential step in cell surface expression (this study and [ 2 ]). In the case of TrkA, this results in two predominant inactive steady state pools, one within the GN and the other at the cell surface (this study and [ 1 - 3 ]) both maintained inactive by a full complement of spontaneous activation inhibitory D4 and D5 IG-like domains, a full N-glycosylated status that reduces aberrant accumulation within the ERGIC, N-glycan maturation that further reduces aberrant intracellular accumulation by promoting translocation to the cell surface [ 1 - 4 , 7 , 8 - 10 ] and, in the case of cell surface TrkA, endogenous PTPase activity [ 2 ]. In contrast to TrkA, immature N-glycosylated 100kDa TrkAIII exits the ER but fails to adequately reach the GN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The marked difference in intracellular trafficking, cell surface expression and spontaneous activation exhibited by TrkA and TrkAIII in SH-SY5Y cells confirms the critical role played exons 6 and 7 encoded sequence in optimising intracellular trafficking from the ER to the GN, reducing intracellular spontaneous activation potential and promoting receptor maturation, an essential step in cell surface expression (this study and [ 2 ]). In the case of TrkA, this results in two predominant inactive steady state pools, one within the GN and the other at the cell surface (this study and [ 1 - 3 ]) both maintained inactive by a full complement of spontaneous activation inhibitory D4 and D5 IG-like domains, a full N-glycosylated status that reduces aberrant accumulation within the ERGIC, N-glycan maturation that further reduces aberrant intracellular accumulation by promoting translocation to the cell surface [ 1 - 4 , 7 , 8 - 10 ] and, in the case of cell surface TrkA, endogenous PTPase activity [ 2 ]. In contrast to TrkA, immature N-glycosylated 100kDa TrkAIII exits the ER but fails to adequately reach the GN.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of intracellular TrkAIII re-localisation for oncogenic activity, identifies the ERGIC/COPI compartment as a preferential site for spontaneous TrkAIII activation and provides an explanation for how TrkAIII, compromised by the omission of the D4 IGC1 spontaneous activation-prevention domain, is able to overcome the threshold for spontaneous activation. The subsequent and altered oncogenic signalling through PI3K/Akt but not Ras/MAPK results in increased survival, a pattern of malignant gene expression, increased genetic instability and promotion of stem cell-like behaviour rather than differentiation [ 1 , 3 , 4 , 6 , 35 ], which together not only promote tumour progression but may also be involved in tumour initiation. TrkA tyrosine kinase inhibitors abrogate this mechanism by promoting the anterograde transport of inactivated TrkAIII to the GN, resulting in GN-associated TrkAIII maturation to a 120kDa form that is degraded at the proteasome, reducing both intracellular accumulation and oncogenic activity of the TrkAIII oncoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merely to NGF interaction in tumor cells, Zhu and coworkers highlighted that the NGF–trkA NGFR interaction influences growth and spread of pancreatic cancer cells, Zhang and coworkers highlighted the prognostic value of NGF-receptors while Missale and coworkers showed the NGF-receptor overexpression associated with a good prognosis [ 39 – 41 ]. Farina and coworkers described a different trkA NGFR isoform (trkA III, the result of an alternative splicing) able to induce an aberrant and aggressive proliferation in neuroblastoma cells [ 42 ]. In a very recent study, Ruggeri and co-workers highlighted that NGF binding to trkA NGFR and TRAIL (TNF-related apoptotis-inducing ligand) might suppress neuroproliferation in neuroblastoma by inducing apoptosis [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al demonstrated that patients with NB exhibiting low expression levels of MYCN and TrkA have a 5-year survival rate of 63.7%, whereas the 5-year survival rate of patients with high expression levels of the two is 88.1% (7). In addition, the alternative TrkAIII splice variant is involved in the pathogenesis of advanced stage human NB through microtubules, which are involved in the promotion and maintenance of NB cells (8). In addition to these reports, NCYM has been observed to act as a cis-antisense gene of MYCN, and contributes to the stabilization of MYCN in human NB by inhibiting GSK3β (9).…”
Section: Introductionmentioning
confidence: 99%